The Relationship Between The Hemodialysis Span and The Stress Level and Sleep Quality of Chronic Kidney Failure Patients In Hemodialysis Room At Tk. III Slamet Riyadi Hospital Surakarta - Rahmad, Muhamad Nur; Sutarman, Sutarman; Kanita, Maria Wisnu; Utami, Yola Kinanthi Wening (Journal of Midwifery and Nursing, 2024)
Hemodialysis will affect stress levels and sleep quality in chronic kidney failure patients. The longer a patient with chronic kidney failure undergoes hemodialysis therapy, the patient's stress level and sleep quality will worsen. The study aimed to analyze the relationship between the term hemodialysis and the stress level and sleep quality of chronic kidney failure patients at Tk.III Slamet Riyadi Hospital, Surakarta. The research adopted a quantitative descriptive analytical design with a cross-sectional approach. The sampling technique used total sampling with 57 respondents. Data collection methods utilized the Depression Anxiety Stress Scale (DASS-42) and Pittsburgh Sleep Quality Index (PSQI) questionnaires. The statistical test operated the gamma test. The results revealed the relationship between the term hemodialysis and stress levels and sleep quality with a p-value of 0.009 and 0.006. It inferred a relationship between the hemodialysis span, stress levels, and sleep quality. The correlation value between variables is 0.431 and 0.410. The longer the hemodialysis, the higher the stress level and the worse the patient's sleep quality (one blank single space line, 9 point font)